ANALYSIS PLANNING AND CONTROL OF NON CREDIT DISTRIBUTION IN LOAN PERFORMING PT.BPR-LPN KOTO DALAM - Nagara, Patria; Afrianti, Rini; Hidayat, Akmal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Singer study conducted to determine the effect a review of Planning and Control lending Against soundness ratio of non-performing loans at PT. BPR-LPN Koto Dalam. Purpose Of Research Singer is to review Test Operations And Operating simultaneous partial influence of Planning and Control lending Against soundness ratio of non-performing loans in PT.BPR-LPN Koto Dalam, used multiple linear regression analysis. The research instruments used test is the test of validity and reliability test. The Classical assumption test used is normality test, test multicollinearity, and heteroscedasticity test. As for the review hypothesis test, F test and t test. The analysis tool used to review the planning and Control Testing the effect of lending against soundness ratio of non-performing loans is a regression WITH 17:00 help SPSS version for windows. Research shows that the planning lending On The Level NOT affect the health of non-performing loans. It indicated WITH Singer t Namely -0176 and 0642 sig> 0.05 And The significant influences of the loan portfolio BETWEEN Control Against Health Level of non performing loan ratio indicated WITH HAL singer t_hitung That 0012 And 0793 sig